2004
DOI: 10.1016/j.joca.2004.05.009
|View full text |Cite
|
Sign up to set email alerts
|

IL-17, IL-1β and TNF-α stimulate VEGF production by dedifferentiated chondrocytes

Abstract: AIM: To evaluated the therapeutic and prophylactic effect of thalidomide on 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced colitis. Thalidomide has been reported to downregulate the expression of tumor necrosis factor α (TNF-α), IL-12, and vascular endothelial growth factor (VEGF), hallmarks of intestinal inflammation in Crohn's disease (CD). METHODS: Male Wistar rats were divided in five groups of ten animals each. Four groups received a rectal infusion of TNBS in ethanol. The first group was sacrificed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 38 publications
5
60
1
2
Order By: Relevance
“…Further, chondrocyte phenotype modulations in OA in the form of dedifferentiation (58,59), proliferation (60), apoptosis (61), and hypertrophy (46,62) have been proposed. We found that many genes (e.g., Ltbp2, Phex, and Reln) were regulated similarly in both degrading cartilage and differentiating chondrocytes, positioning mechanisms leading to hypertrophic differentiation of chondrocytes in early OA.…”
Section: Discussionmentioning
confidence: 99%
“…Further, chondrocyte phenotype modulations in OA in the form of dedifferentiation (58,59), proliferation (60), apoptosis (61), and hypertrophy (46,62) have been proposed. We found that many genes (e.g., Ltbp2, Phex, and Reln) were regulated similarly in both degrading cartilage and differentiating chondrocytes, positioning mechanisms leading to hypertrophic differentiation of chondrocytes in early OA.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that IL-22 and TNF-α represent the key combination of cytokines expressed by Th22 cells that unlocks the activation of keratinocytes, as in vitro cultures using either Th22 supernatants or a combination of IL-22 and TNF-α maximally induced the Th22 signature in keratinocytes, whereas anti-IL-22 did not fully block - and recombinant IL-22 alone was not sufficient to induce - expression of these genes. This dual key is a recurring scheme observed in the lymphoid regulation of tissue cells in inflammatory context, such as the regulation of epithelial cells by IL-17, which is only maximal in synergism with IFN-γ, IL-1, or TNF-α (42,43). In contrast to major effects on the innate immune response by keratinocytes in a proinflammatory context, IL-22 and TNF-α did not synergize in the enhanced wound healing clearly induced by Th22 cells.…”
Section: Figurementioning
confidence: 94%
“…We can envision a couple of mechanisms (not mutually exclusive) by which TLR stimulation could influence angiogenic growth factor production in PBMCs: (i) a direct effect on VEGF and angiopoietin production and/or (ii) an indirect effect due to TLR-induced proinflammatory cytokine production. Proinflammatory cytokines, including tumor necrosis factor alpha (TNF-␣) and IL-17, are known inducers of VEGF proteins (13), and hence an indirect effect of TLR stimulation on angiogenic growth factor production cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%